Membangun Mahasiswa yang Berkarakter Melalui Karya Seni - Fauzul Asni (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This article aims to explain about the alternative of reconstructing characterized education through artwork for students at State University of Padang (UNP). The artwork is an expression in which human being is able to express moral values through its symbols; as a result, it becomes expressive media for the characterized education. This research is the qualitative one which applies the descriptive method. The data is collected through direct observation, interview and library research. Afterward, the data were analyzed by using phenomenology approach. Apparently, the problem of the students at UNP is the lack of characters. As the cultural and social beings who live in the surroundings of tradition and cultural philosophies like Minangkabau, whose famous sayings adat basandi sarak, sarak basandi kitabullah (culture is based on religion, and the religion is based on Islam), these students cannot contain themselves being in the society. On the other side, artwork as an expressive media of human’s behavior and feelings is viewed as means of delivery the concepts of characterized education for these students; in return, they can behave as what is expected by culture and tradition of Minangkabau. Keywords: characterized education, artwork, the tradition and culture of Minangkabau